2017
DOI: 10.7554/elife.20444
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling (SOCS)5 ameliorates influenza infection via inhibition of EGFR signaling

Abstract: Influenza virus infections have a significant impact on global human health. Individuals with suppressed immunity, or suffering from chronic inflammatory conditions such as COPD, are particularly susceptible to influenza. Here we show that suppressor of cytokine signaling (SOCS) five has a pivotal role in restricting influenza A virus in the airway epithelium, through the regulation of epidermal growth factor receptor (EGFR). Socs5-deficient mice exhibit heightened disease severity, with increased viral titres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 62 publications
(91 reference statements)
0
50
0
1
Order By: Relevance
“…Previous data showed that, SOCS5 mRNA was significantly upregulated in response to H1N1, H3N2, H5N1, and H11N9. Suppressing SOCS signals improved influenza infection and inhibited HRSV replication [68,69]. CCR2 mRNA upregulation was correlated with HRSV-disease severity [70].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data showed that, SOCS5 mRNA was significantly upregulated in response to H1N1, H3N2, H5N1, and H11N9. Suppressing SOCS signals improved influenza infection and inhibited HRSV replication [68,69]. CCR2 mRNA upregulation was correlated with HRSV-disease severity [70].…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were lyophilized to dryness using a Savant AES 1010 SpeedVac (GMI, Ramsey, MN, USA) and reconstituted in 150 μL 2% acetonitrile/0.1% trifluoroacetic acid. Mass spectrometry analysis was performed as previously described . Acidified peptide mixtures (2 μL) were analyzed by nanoflow reversed‐phase liquid chromatography tandem mass spectrometry on an EASYNano LC 1200 (Thermo Fisher, Bremen, Germany) coupled to a Q Exactive Orbitrap mass spectrometer (Thermo Fisher).…”
Section: Methodsmentioning
confidence: 99%
“…The FLAG‐tagged human Riplet construct was obtained from GenScript in a pcDNA 3.1 expression vector. Constructs for exogenous expression of TRIM25 and Riplet were similarly transfected into BCi‐NS1.1 cells 24 h prior to infection . IAV H1N1 (A/Auckland/1/2009) was diluted in the appropriate serum‐free media and added to cells at a multiplicity of infection of 5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NF‐κB is also regulated by PHD (primarily PHD1), which reveals a common molecular pathway connecting hypoxia‐dependent regulation of HIF‐1 and NF‐κB . However, it remains unclear when CS‐induced HIF‐1α activation/overexpression and related pathology become important in the human disease course, which needs further investigation in experimental mouse models that recapitulate human disease features, and confirmed in prospective human studies …”
Section: Hypoxaemia and Hypoxia In Copdmentioning
confidence: 99%